Efforts to Improve Children's Health After Circumcision Through Flash Card Games : Upaya Peningkatan Kesehatan Anak Pasca Khitan Melalui Permainan Flash Card (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2024)
The importance of understanding the health impacts after circumcision cannot be underestimated. Medically, circumcision has certain benefits and risks, and post-circumcision care is a crucial step to ensure optimal recovery. The aim of this health education is to increase children's understanding in efforts to improve children's health after circumcision through flash card games. The method is through flash card games with children, and with parents through lectures, questions and answers, discussions. Evaluation through pretest and posttest. The respondents in this study were 15 post-circumcision children and parents in Sukoreno Village, Kalisat District, Jember Regency. The results showed that there was an increase in respondents' knowledge before and after education with an average score of 60 to 80. Community service was well received by parents, post-circumcision children, health workers and village officials. Children feel happy, because children learn with fun techniques, namely playing. Flash cards are a medium that can be used in education for school-aged children.